Application of Big Data Technology in Network Security Analysis - Miao, Jinli (Journal of Theory and Practice of Engineering Science, 2025)
China is gradually entering the era of big data and information. In this context, with the continuous popularization and updates of Internet technology, network security issues have been receiving increasing attention. There are many risks and hidden dangers in practical networks. Therefore, network security technology is facing significant threats and challenges. The current network environment in China is still relatively complex. On the one hand, it facilitates peoples lives and work, but on the other hand, it also poses many risks to property and personal safety.